Awareness about Knowledge, Attitudes, and Preventive Practices related to COVID-19 at a Public Sector University of Larkana: Knowledge, Attitudes, and Preventive Practices related to COVID-19 - Ullah, Saif; Micah, Sineer; Raja, .; Kumar, Santosh (Pakistan Journal of Health Sciences, 2023)
The existence of the COVID-19 lethal virus highlights the urgent need to create a comprehensive awareness campaign for implementing infection control methods to lower the disease prevalence of this rapidly spreading infection. Objective: To determine the level of awareness about knowledge, attitudes, and preventive practices related to COVID-19 among faculty members at a medical university in Larkana. Methods: A descriptive cross-sectional study was conducted on 284 participants of any age group and both genders by using a simple random sampling technique. Data analysis was performed by using the Statistical Package for Social Sciences. Categorical data were presented in the form of frequency and percentages, while, continuous data were shown in the median and interquartile range. Results: The results demonstrated that 66.2% were male, and almost half, 49.3% of the participant’s age group was 31-40 years. 94% of the participants had good knowledge, 67% had a good attitude, and 88% had good preventive practices, 69% believed that lack of awareness could cause difficulty in halting the spread of COVID-19. Social media (61.6%) followed by friends and family (24.3%) were the first sources to learn about the disease. Conclusions: Most of the respondents had good knowledge, attitude, and practice of COVID-19. Social media and other online platforms were the participants’ major information sources